Konseling Gizi Ibu Hamil Anemia Untuk Meningkatkan Status Kesehatan Maternal Di Praktek Bidan Mandiri - Diana Putri (STIKES Columbia Asia Medan, 2025)
Anemia in pregnancy is still a major problem experienced by almost half of pregnant women in all countries in the world including Indonesia. Many pregnant women refuse and do not comply with taking FE tablets for various reasons so that the prevalence of anemia in pregnant women is still high. A mother is said to be compliant with taking FE tablets if ≥ 90 % of the amount should have been taken. Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community, and has a very large impact on the quality of human resources, which is called